Study of heart rate variability in healthy humans as a function of age: considerations on the contribution of the autonomic nervous system and the role of the sinoatrial node - Tasé, David Alejandro Jorge (2025)
This study focused on the complex structure of heart rate variability (HRV) in the healthy heart. We studied the behavior of the heart rate variability (HRV) in healthy humans as a function of age from conception, including fetal data. We calculated statistical quantities such as the mean value of RR intervals (<RR>), the standard deviation of these intervals (SD), the power of the very low frequency (VLF), low frequency (LF) and high frequency (HF) bands, and the large-scale properties of HRV. We rationalized our findings discussing previous results that identify the signatures of the sinoatrial node (SAN) and the autonomic nervous system (ANS) in the HRV. This work provides further insights into the contribution of the SAN and the ANS to the cardiac rhythm in humans.